2017
DOI: 10.2147/cia.s121467
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lower limb position and pelvic floor muscle surface electromyography activity in menopausal women: a prospective observational study

Abstract: ObjectivesIn physiotherapeutic practice, special attention is being given to the reciprocal anatomical, physiological, and biomechanical relationship of the pelvis and the structures connected to it. However, the scientific literature shows mainly the theoretical information about their mutual connections. The lack of information about these relations from a practical aspect coupled with the paucity of scientific papers on the impact of posture changes on the pelvic floor led the authors to conduct this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Third, whilst the RTA was examined in the left lateral position, the MRI sequence from which the anatomical models were delineated from was conducted in the supine position. Whilst there is evidence in the literature that hip flexion alters the anorectal angle [15] as well as the activity and functionality of the pelvic floor [16], there is little to none empirically quantifying the degree or nature of alteration in the left lateral position when compared with the standard supine position. The complexity of this issue is compounded by the fact that merely moving the position of the body from left lateral to supine, even without flexion of the hips, has in itself been found to significantly move some elements of the abdominal and pelvic anatomy [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Third, whilst the RTA was examined in the left lateral position, the MRI sequence from which the anatomical models were delineated from was conducted in the supine position. Whilst there is evidence in the literature that hip flexion alters the anorectal angle [15] as well as the activity and functionality of the pelvic floor [16], there is little to none empirically quantifying the degree or nature of alteration in the left lateral position when compared with the standard supine position. The complexity of this issue is compounded by the fact that merely moving the position of the body from left lateral to supine, even without flexion of the hips, has in itself been found to significantly move some elements of the abdominal and pelvic anatomy [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…PFM activity increases when sitting from the supine position and increases further when standing [4,24,25]. The supine position is more stable than the standing or sitting position because it has a wide BOS and lower center of gravity [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the effect of pelvic tilt on PFMs activity [20] and synergistic muscles [19,23,24]. Ptaszkowski et al [19], Ptaszkowski et al [23], Halski et al [24] studies showed higher bioelectric activity of adductor magnus, rectus abdominis, and gluteus maximus muscles at the posterior pelvic tilt than at the anterior pelvic tilt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Furthermore, a previous study in menopausal study reported that PFM function depends on various lower limb positions, and that the supine position is recommended for diagnosis of weakened PFM. 22 Therefore, assessing PFM and other synergists functions simultaneously in a supine position should be performed in further studies.…”
Section: Discussionmentioning
confidence: 99%